Slovenia: The End of a Success Story? When a Partial Reform Equilibrium Turns Bad. Issue 2 (7th February 2016) - Guardiancich, Igor
Abstract: During the Great Recession, Slovenia recorded one of the worst economic performances within the EU. Such a decline is surprising as the country was the most stable among the post-socialist states. The article individuates the root cause for the downfall in protracted reform gradualism, which resulted in an inefficient privatisation process. This locked the country into a 'partial reform equilibrium' where economic elites extracted rents. Following accession to the EU, the unsustainable lending practices of state-owned banks to corporate organisations and the gridlock in policymaking pushed the country into an economic and political 'bad equilibrium' . Even though the Slovenian export sector proved to be surprisingly resilient, a massive debt overhang and a huge reform backlog are still weighing down on a healthy recovery.